2023
DOI: 10.1097/rli.0000000000000949
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the Potential of Photon-Counting CT in Abdominal Imaging

Abstract: Photon-counting computed tomography (PCCT) imaging uses a new detector technology to provide added information beyond what can already be obtained with current CT and MR technologies. This review provides an overview of PCCT of the abdomen and focuses specifically on applications that benefit the most from this new imaging technique. We describe the requirements for a successful abdominal PCCT acquisition and the challenges for clinical translation. The review highlights work done within the last year with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 87 publications
(142 reference statements)
0
10
0
Order By: Relevance
“…To date, already several studies have shown advantages of PCD-CT over conventional CT, [6][7][8] including applications for abdominal, vascular, cardiac, or chest imaging and various other fields of radiology may benefit from the new detector technique. [9][10][11][12] In this review, we summarize the current status of PCD-CT with regards to applications focusing on the central nervous system and the head and neck region. We review the existing literature and highlight promising future applications.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To date, already several studies have shown advantages of PCD-CT over conventional CT, [6][7][8] including applications for abdominal, vascular, cardiac, or chest imaging and various other fields of radiology may benefit from the new detector technique. [9][10][11][12] In this review, we summarize the current status of PCD-CT with regards to applications focusing on the central nervous system and the head and neck region. We review the existing literature and highlight promising future applications.…”
mentioning
confidence: 99%
“…The benefit of these new, technically guided opportunities is subject of intensive ongoing research. To date, already several studies have shown advantages of PCD-CT over conventional CT, 6–8 including applications for abdominal, vascular, cardiac, or chest imaging and various other fields of radiology may benefit from the new detector technique 9–12 . In this review, we summarize the current status of PCD-CT with regards to applications focusing on the central nervous system and the head and neck region.…”
mentioning
confidence: 99%
“…12 Dr Fides Schwartz from the Duke University Medical Center explores the possibilities and potential of photon-counting detector CT in abdominal imaging. 13 Dr Joachim Wildberger from the Maastricht University discusses the current experience and research on the new horizons in vascular imaging with photon-counting detector CT, 14 whereas Dr Zsarnoczay and colleagues from the Medical University of South Carolina, Charleston explore the new options for characterizing the heart and myocardium with photon-counting detector CT. 15 Finally, Dr Gregor Jost and colleagues from the Bayer AG, Berlin detail the current research and future developments on new contrast agents for k-edge imaging tailed to photon-counting detector CT. 16 We are grateful to each author for their contributions, for their dedication, their scientific approach in exploiting the potential of this new technique, and for their ability to explain this new technology to the readers in an understandable fashion and with impressive illustrations. We believe that the review articles of this special issue will serve as long-term references for current and future physicians, physicists, and scientists alike.…”
mentioning
confidence: 99%
“…Dr Martine Remy-Jardin from the Heart and Lung Institute, Lille Cedex describes the potential and clinical applications of high-resolution photon-counting detector CT imaging of the chest and lung 12 . Dr Fides Schwartz from the Duke University Medical Center explores the possibilities and potential of photon-counting detector CT in abdominal imaging 13 . Dr Joachim Wildberger from the Maastricht University discusses the current experience and research on the new horizons in vascular imaging with photon-counting detector CT, 14 whereas Dr Zsarnoczay and colleagues from the Medical University of South Carolina, Charleston explore the new options for characterizing the heart and myocardium with photon-counting detector CT 15 …”
mentioning
confidence: 99%
“…Recently, the first dual-source photon-counting detector CT (PCD-CT) became available for clinical use 21–25 . With the introduction of PCD-CT, a novel reconstruction algorithm called virtual noniodine (VNI) images, which is based on a decomposition of iodine and calcium as base materials, became clinically available.…”
mentioning
confidence: 99%